Colonización y recomposición campesina en el Guaviare, 1960-1998 - Marín Taborda, Jorge Iván (Pontificia Universidad Javeriana, 2014)
One of the driving factors of colonization is made up the problem of land distribution, which affects in a significant manner many sectors of the peasantry. The colonization of what today is the state of Guaviare possesses specific characteristics that indicate a process of peasant occupation -coming from, almost exclusively, Andean small farmastead-that, within a period of three decades, has constituted the base of peasant recomposition.